Lojalność urzędnika w świetle prawa i etyki - Kasiński, Michał (Annales. Etyka w Życiu Gospodarczym, 2010)
Officials in a democratic state should be its society's loyal servants, bound to respect the law. They are also bound to be loyal for the supervisors, and obedient to their orders. The Author analyzes legal regulation concerning conflicts which arise from that „double loyalty” of the officials, especially when the orders they are given contradict legal regulation or principles of ethic they find binding.